PESAN MORAL PADA KARYA FOTO JURNALISTIK TENTANG PARIWISATA INDONESIA DI E-MAGAZINE NATIONAL PESONA INDONESIA - Agnes Lidia herlina Nggili; Monika Wutun; Henny L.L.Lada (Jurnal Ranah Komunikasi, 2023)
This study examines the communication message in photos of beach tourism destination on Lombok Island in the Pesona Electronics Magazine (Pesona E- Magazine). This research used qualitative method with semiotic analysis according to Charles Sanders Pierce Model. This research focus to found the meaning of photos journalism communicated within the lombok beach photos and analyzed by sign, interpretant and object. The results of the study show that the presentation of Indonesian tourism photos does not only hone the skills of photographing or writing for journalists and photo editors, but also presents photos that have aesthetic value that can convey messages and be accepted by audiences with various views. Photos in e-magazine Pesona fulled by coloring pictures has the values contained therein. Researchers analyzed four beach tourism photos contained in the e-magazine using Pierce's semiotic analysis. Through this semiotic process, it produces interpretations that mostly describe moral messages. The depiction of a moral message in the four photos of beach tourism in this Pesona e-magazine, namely, the importance of cleanliness in the coastal environment, especially beaches which have object values that can attract the attention of tourists, because clean tourist attractions have a positive impact on living things and can be a special attraction. To every tourist who wants to visit and protect coral reef ecosystems because coral reefs are marine ecosystems that have a positive impact on living things.